Analysis of the Dynamic Active Earth Pressure from c-φ Backfill Considering the Amplification Effect of Seismic Acceleration - Zhiliang Sun; Wei Wang; Hanghang Liu (Applied Sciences)
This study extends the method of pseudo-dynamic analysis based on the Mononobe-Okabe (M-O) method by comprehensively incorporating the seismic acceleration response characteristics of backfill soil and the cohesive properties of the fill. The proposed method is adapted for backfill soils by incorporating the cohesion c and internal friction angle φ (including scenarios with non-horizontal backfill surfaces). Theoretical formulas for the active earth pressure coefficient and its distribution on rigid retaining walls under the most unfavorable conditions are derived. The rationality of the proposed formulas is preliminarily verified using model test data from the relevant literature. A detailed parametric sensitivity analysis reveals the following trends: The active earth pressure coefficient Ka increases with increases in the amplification factor fa, wall backface inclination angle θ, backfill slope inclination i, lateral vibration period T, and horizontal seismic acceleration coefficient kh; Ka decreases with an increasing internal friction angle φ and cohesion/unit weight ratio c/γH. The failure wedge angle αa increases with increases in φ, θ, and c/γH, decreases with increases in fa, the soil–wall friction angle δ, i, T, kh, and the vertical seismic acceleration coefficient kv. Calculations are carried out to further identify the critical tensile stress depth in cohesive backfill soils using c and φ. The proposed analysis highlights the necessity of considering the seismic acceleration amplification factor fa, backfill cohesion c, and soil–wall adhesion cw in active earth pressure calculations. This study recommends that the seismic design of retaining walls should involve appropriate evaluation of the the actual cohesion of backfill materials and fully account for the acceleration amplification effects under seismic loading.